2023
DOI: 10.3390/molecules28093759
|View full text |Cite
|
Sign up to set email alerts
|

The Differences of Nutrient Components in Edible and Feeding Coix Seed at Different Developmental Stages Based on a Combined Analysis of Metabolomics

Abstract: Coix lachryma-jobi L. is an excellent plant resource that has a concomitant function for medicine, foodstuff and forage in China. At present, the commonly used cultivar for both medicine and foodstuff is Xiaobaike, and the cultivar for foraging is Daheishan. However, differences in the internal composition of plants lead to the expression of different phenotypic traits. In order to comprehensively elucidate the differences in nutrient composition changes in Coix seeds, a non-targeted metabolomics method based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Fingerprinting of Coicis semen from dried tissues using the sequence-independent microarray ( Niu et al, 2013 ) and the high-performance liquid chromatography (HPLC)-evaporative light scattering detector ( Du et al, 2021 ) has been reported. It contains more than 80 active components including polysaccharides, fatty acids (FAs), phenolic acids, sterols, lipids, flavonoids, triterpenes, alkaloids, and adenosine ( Zhu, 2017 ; Yu J. et al, 2022 ; Huang et al, 2022 ; Pan et al, 2023 ; Wei et al, 2023 ). The HPLC-atmospheric pressure chemical ionization-mass spectrometry (MS) method identified 12 triacylglycerols in coix oil ( Xiang et al, 2005 ).…”
Section: The Cardiovascular Protective Activity Of Yyfzmentioning
confidence: 99%
“…Fingerprinting of Coicis semen from dried tissues using the sequence-independent microarray ( Niu et al, 2013 ) and the high-performance liquid chromatography (HPLC)-evaporative light scattering detector ( Du et al, 2021 ) has been reported. It contains more than 80 active components including polysaccharides, fatty acids (FAs), phenolic acids, sterols, lipids, flavonoids, triterpenes, alkaloids, and adenosine ( Zhu, 2017 ; Yu J. et al, 2022 ; Huang et al, 2022 ; Pan et al, 2023 ; Wei et al, 2023 ). The HPLC-atmospheric pressure chemical ionization-mass spectrometry (MS) method identified 12 triacylglycerols in coix oil ( Xiang et al, 2005 ).…”
Section: The Cardiovascular Protective Activity Of Yyfzmentioning
confidence: 99%